Equitable and Sustainable Economy: A Study on the Relevance of the Low-Carbon Economy to Maslahah Mursalah - Ulya, Husna Ni'matul; Humaidi, Muchtim; Abdullah, Umar; Frafika Sari, Ima (Journal of Islamic Economics and Finance Studies, 2025)
This study examines the environmental consequences of unsustainable economic growth by exploring the alignment between low-carbon economic initiatives and the Islamic principle of maslahah mursalah. The research is motivated by widening the gap between environmental degradation and ethical responsibility in economic development. The objective is to analyze how low-carbon policies correspond with Islamic economic objectives grounded in the pursuit of public benefit. This study employs a qualitative research approach, using documentary analysis, of policy documents, academic literature, and reports on low-carbon economic policies and maslahah mursalah. Through content analysis, this study investigates the relationship between low-carbon economic objectives and maslahah mursalah by identifying key themes and patterns in the literature. The findings reveal that low-carbon policies, which aim to reduce emissions and foster sustainable growth are consistent with maslahah mursalah as they prevent environmental harm that threatens human week-being. These policies address maslahah across the levels of dharuriyah (necessities), hajiyyat (complementary needs), and tahsiniyyat (enhancements). Furthermore, transitioning to a low-carbon economy supports   long-term economic resilience and ecological balance, thereby reinforcing the ethical obilation to safeguard the welafare of future generations. This study contributes to the field of Islamic economic by demonstrating the applicability of maslahah mursalah in confronting contemporary environmental and developmental challenges.